COMPEREHENSIVE TECHNICAL STUDIES OF FLOOD CONTROL OVER SOLO CITY AREA (CASE STUDY IN DEMANGAN BARRAGE) - Ali Trusharyanto; Rachmad Jayadi; Darmanto Darmanto (Journal of the Civil Engineering Forum, 2013)
City of Surakarta, known as Solo City is one of cities in Central Java Province traversed by Bengawan Solo River. Heavy rainfall in upstream area of Bengawan Solo River causes increase in high water level at downstream. Bengawan Solo River will be higher than water level in drainage system which may induce a backwater flow. Since Colonization era, the government has built dikes and barrages against backwater flow and inundation problem. One of the barrages was Demangan Barrage dividing river flow into Bengawan Solo River and Pepe River. It was equipped with total capacity pump of 12,3 m3/s. The inundation is not only caused by the backwater flow coming from Bengawan Solo River, but also surface runoff as the result of the excess rainfall which cannot be drained gravitationally to the main river if the gate was closed. Therefore, comprehensive study combining hydrology and hydraulics analysis is highly needed in order to achieve more effective flood control management.Hydrology analysis was done to estimate the direct runoff hydrograph from catchment area in Solo City to downstream of Pepe River. While in hydraulics case, hydraulic parameter in downstream of Pepe River influenced by Bengawan Solo River stream was analyzed. Both studies were simulated using software HEC-RAS 4.1.0 version. The simulation considered drainage channel, gate, pump system and dike in Pepe River downstream.Simulation using 10 years of return period in Solo City and average annual water level in Bengawan Solo River showed that Pepe River can flow through the gate, while the highest water level is still below the dike. Simulation considering 10 years of return period, water level hydrograph of Bengawan Solo River, existing pump, and gate operation inferred that Pepe River surpassed top of dike. Capacity of required pump should be more than 168,3 m3/s in order to pass 10 years of return period. By combining operational of existing pump and dike elevated up to +87,63 m, capacity of required pump became lesser which was approximately 120,3 m3/s. Simulation of HEC-RAS conducted by operating pump automatically on critical elevation without heightened dike obtained the total capacity of pump was 132,3 m3/s.Keywords: barrage, pump operation, Bengawan Solo River, flood control management.